(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The study shows how these methods influence the novella’s thematic concerns—struggle, loneliness, and human dignity—through attentive reading and linguistic analysis. The research also discusses Hemingway’s language choices’ wider ramifications within the framework of modernist literature and how they enhance the text’s emotional resonance and psychological depth. Linguists, literary analyzers, and everyone else interested in the relationship between language structure and literary effect will find this study to be useful.